On the comparison of lightning fatality rates between states in Malaysia from 2008-2019 - A Rahim, Syakura; Izadi, Mahdi; Osman, Miszaina; Ab Kadir, Mohd Zainal Abidin; Abu Bakar, Elistina; Gomes, Chandima; Jasni, Jasronita (IEEE, 2019)
This study briefly canvasses lightning fatalities in Malaysia. Acquiring lightning fatality statics are a challenge as mandatory reporting of such events is seldom required, and as such, many lightning incidences were unreported. For that reason, numerous cases were undocumented in the official records. However, for injury prevention efforts and calling a government's attention to these as a severe problem, information on numbers, exposed locations and their backgrounds are essential to determine vulnerable areas. A theoretical approach using Gomes-Kadir equation was also tested to estimate annual lightning deaths in each state of Malaysia using lightning density and sociological factors and the results compared against known fatality data.